Familial and genetic association with neurodevelopmental disorders caused by a heterozygous variant in the SRRM2 gene - Zhang, Tao; Xu, Lei; Zhu, Hongdan; Ying, Yuyi; Ding, Jinlong; Ding, Haigang; Shi, Xiaoliang; He, Yao; Jin, Xin; Xia, Guiyu (Frontiers in Endocrinology, 2023)
Background Neurodevelopmental disorders (NDDs) are a class of disorders affecting brain development and function, characterized by an inability to reach cognitive, emotional, and motor developmental milestones. The pathology of NDDs is complex. A recent study found that variants in the SRRM2 gene cause NDDs. However, genetic conditions play the most important role in the etiology of NDD. The genetic causes of NDD are extremely heterogeneous, leading to certain challenges in clinical diagnosis. Methods A pregnant woman with congenital intelligence disorder came to our hospital for genetic diagnosis to predict the status of her fetus. Her mother and a brother also suffer from congenital intelligence disorder. She has a daughter with speech delay. Whole exome sequencing was used to identify a mutation (c.1415C>G) in the SRRM2 gene of this family that resulted in a change in the 472nd amino acid residue of the SRRM2 protein from serine to terminated. Conclusion We report a family with an autosomal dominant genetic disorder caused by variants in the SRRM2 gene causing NDDs. Prenatal diagnosis can help patients with this genetic disorder to have healthy offspring.